Oscillations microhardness crystal alloy Al-1 in the process of fatigue - Корчук, О.Ю. (Proceedings of National Aviation University (archive), 2008)
The regularity of the microhardness oscillation of the crystallites with face centered cube lattice under fatigue loading, that are determined by the correspondent bifurcation points of the fatigue process. Relationship between periodicity of the microhardness oscillation and crystallographic orientation is proved. Common dependence of the load cycle number to the origin of the base bifurcation points on the resolved shear stresses, that act in the crystal and on the crystallographic orientation are obtained.